Enhancement of time-domain acoustic imaging based on generalized cross-correlation and spatial weighting. (15th June 2016) - Quaegebeur, Nicolas; Padois, Thomas; Gauthier, Philippe-Aubert; Masson, Patrice
Abstract: In this paper, an alternative formulation of the time-domain beamforming is proposed using the generalized cross-correlation of measured signals. This formulation uses spatial weighting functions adapted to microphone positions and imaging points. The proposed approach is demonstrated for acoustic source localization using a microphone array, both theoretically and experimentally. An increase in accuracy of acoustic imaging results is shown for both narrow and broadband sources, while a factor of reduction up to 20 in the computation time can be achieved, allowing real-time or volumetric source localization over very large grids. Abstract : Highlights: An alternative formulation of the time-domain beamforming is proposed. Generalized Cross-Correlation (GCC) is used instead of Cross-Correlation operator. A spatial weighting function is introduced to sharpen the imaging result. Numerical and experimental validation is proposed for multiple sources localization.